2020
DOI: 10.1159/000511907
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Endoscopic Features of Raspberry-Shaped Gastric Cancer in Helicobacter pylori-Uninfected Patients

Abstract: <b><i>Background:</i></b> Gastric adenocarcinoma of foveolar type (GA-FV) is a raspberry-shaped gastric cancer (RSGC) and garners much attention as <i>H. pylori</i> (<i>Hp</i>)-uninfected gastric cancer. However, the classification and clinicopathological and endoscopic features of RSGCs in <i>Hp</i>-uninfected patients are poorly defined. We designed a new histopathological classification of RSGC and compared them via endoscopic and clinicopathologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(28 citation statements)
references
References 20 publications
5
23
0
Order By: Relevance
“…However, it is necessary to understand the characteristics of each type, since these findings tend to be few for GA-FG, which has an atypical color and morphology, such as a reddish color and flat or depressed type. In particular, reddish and of an elevated type lesions ( Figure 4 a–c) required differentiation from a gastric foveolar-type adenoma (raspberry-shaped gastric cancer in Japan) [ 24 , 25 ]. In contrast, the percentage of GA-FGM lesions showing the above four features was generally low.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to understand the characteristics of each type, since these findings tend to be few for GA-FG, which has an atypical color and morphology, such as a reddish color and flat or depressed type. In particular, reddish and of an elevated type lesions ( Figure 4 a–c) required differentiation from a gastric foveolar-type adenoma (raspberry-shaped gastric cancer in Japan) [ 24 , 25 ]. In contrast, the percentage of GA-FGM lesions showing the above four features was generally low.…”
Section: Discussionmentioning
confidence: 99%
“…Although H. pylori –uninfected GC is reported to account for less than 1% of all GCs, 1 its incidence has varied widely from 0.66% to 14% in previous reports. 6 11 The incidence of H. pylori infection is decreasing rapidly in younger age groups, and the number of reports of H. pylori –uninfected GC is expected to relatively increase in the future. Although a definition of H. pylori –uninfected GC has yet to be established, Matsuo et al 1 defined it as a case in which (1) two or more diagnostic methods (such as serum H. pylori antibody and stool, urine, and UBTs) are negative, (2) histopathological examination shows no gastritis, and (3) endoscopic examination shows no atrophy (with RAC).…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al 7 reported four further cases, including the intestinal type. In recent years, there have been increasing reports of foveolar-type tumors characterized by small reddish elevated lesions, 8 , 9 which Nomura et al 10 called “raspberry-like” tumors because of their morphology. The location of GC was divided into the upper one-third (U), middle one-third (M), and lower one-third (L) of the stomach.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemically, tumor cells were positive for MUC5AC and negative for MUC6, MUC2, or CD10. Although the Ki67 index was relatively high, p53-positive cells were scattered in the tumor (wild-type pattern) [26]. Although some reports describe these neoplasms as adenocarcinoma, some authors describe these neoplasms as “adenoma” because of their low malignant potential [27].…”
Section: Gastric Carcinoma Arising From Mucosa Without H Pylori Infectionmentioning
confidence: 99%